Theoretical and Methodological Considerations for Research on Eating Disorders and Gender - Springmann, Marie-Luise; Svaldi, Jennifer; Kiegelmann, Mechthild (Frontiers in Psychology, 2020)
Gender is a relevant factor in the etiology of eating disorders (ED) as evidenced by gender-specific components of disordered eating and by the high risk of ED among transgender individuals, in addition to other factors. However, research on connections between eating disorders and gender identity are limited. Researchers who produce explanatory models, content themselves with faulting the sociocultural ideal of slimness for women, but they fail to grasp the connection between culture, gender and the body and they fall short of integrating this perspective into existing psychological knowledge about ED. Psychological research informed by feminist theory has begun to bridge this gap, but this growing area of research needs to be further developed and should include an understanding of ED in persons with all gender identities. This article expands the discussion of gender and ED, by grounding ED in an understanding of gender itself and by discussing methodological implications of this understanding.